Performance-Based Assessments of Functional Cognition in Adults, Part 1—Assessment Characteristics: A Systematic Review. - Lee, Yejin; Randolph, Samantha B.; Kim, Moon Young; Foster, Erin R.; Kersey, Jessica; Baum, Carolyn; Connor, Lisa Tabor (American Journal of Occupational Therapy)
Importance: Although the construct of functional cognition is central to the practice of occupational therapy, there is no consensus regarding the core characteristics of functional cognitive assessments. Thus, it is necessary to review existing performance-based assessments of functional cognition and describe their characteristics to understand how functional cognition is measured and has been conceptualized. Objective: To identify performance-based assessments of functional cognition in adults and describe their characteristics. Data Sources: A literature search was conducted in the MEDLINE, Embase, CINAHL, PsycINFO, Web of Science, and Scopus databases from inception to February 2022. Study Selection and Data Collection: We searched for performance-based assessments that involve direct observation of the performance of everyday activities to assess integrated cognitive skills, referred to as functional cognition, in adults. We used a standardized spreadsheet to extract the characteristics of the included assessments (e.g., construct originally targeted, activities and scoring metrics used). Findings: We identified 25 assessments; most were originally designed for measuring executive functioning. Common instrumental activities of daily living included were cooking and meal preparation, managing finances, using the telephone, and managing medication. Performance time (time taken to complete the task) was frequently used as a scoring metric. Most assessments incorporated observable indicators of functional cognitive abilities (e.g., the task is accurately performed, the task is completed, the task is performed in an efficient and safe way). Conclusions and Relevance: The findings of this review can guide occupational therapy professionals in better understanding functional cognition by illustrating how it is conceptualized in existing assessments. Plain-Language Summary: The objective of this review was to identify and examine the characteristics of performance-based assessments that involve direct observation of the performance of everyday activities to assess integrated cognitive skills, referred to as functional cognition, in adults. We identified 25 assessments. Actual or simulated daily activities used as part of the assessments included cooking and meal preparation, managing finances, using the telephone, and managing medications. These activities are all known to be key to independent community living. Performance time and number and types of errors were frequently used as scoring metrics. Most assessments incorporated indicators of functional cognitive abilities, such as the number of completed or failed tasks or whether the tasks were efficiently performed (i.e., the use of effective strategies). These performance-based assessments provide a standardized way to measure the dynamic integration of cognitive abilities during the performance of everyday activities (i.e., functional cognition). The authors reviewed and describe the characteristics of existing performance-based assessments of functional cognition in adults to understand how functional cognition is conceptualized and measured.